2009
DOI: 10.1063/1.3105944
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation mechanism of dislocation half-loop arrays in 4H-silicon carbide homoepitaxial layers

Abstract: A model is presented for the formation mechanism of dislocation half-loop arrays formed during the homoepitaxial growth of 4H-SiC. The reorientation during glide of originally screw oriented threading segments of basal plane dislocation (BPD) renders them susceptible to conversion into sessile threading edge dislocations (TEDs), which subsequently pin the motion of the BPD. Continued glide during further growth enables parts of the mobile BPD to escape through the surface leaving arrays of half loops comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 18 publications
5
38
0
Order By: Relevance
“…1 (a) reveals the presence of pairs of additional linear features which are slightly inclined to the ID segments. The Burgers vector associated with these features is also 1/3 [11][12][13][14][15][16][17][18][19][20]. These features are also clearly visible in Fig.…”
Section: "Post Mortem" Studies Of Id and Hlasmentioning
confidence: 92%
See 3 more Smart Citations
“…1 (a) reveals the presence of pairs of additional linear features which are slightly inclined to the ID segments. The Burgers vector associated with these features is also 1/3 [11][12][13][14][15][16][17][18][19][20]. These features are also clearly visible in Fig.…”
Section: "Post Mortem" Studies Of Id and Hlasmentioning
confidence: 92%
“…These configurations comprise two straight, screw-oriented BPD segments (with Burgers vector along the offcut direction, i.e. 1/3 [11][12][13][14][15][16][17][18][19][20], as determined by their invisibility on the [1-100] reflection, not shown here) in the substrate, connected to two ID segments, which in turn are connected to two mobile segments on the basal plane of the epilayer. The lower ends of the straight, screw oriented segments in the substrate are invariably connected to complex BPD nodes that apparently have provided pinning points.…”
Section: "Post Mortem" Studies Of Id and Hlasmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The recombination activities of dislocations in 4H-SiC homoepitaxial layers were reported to be stronger in the order of BPDϾ TSDϾ TED. 11 Recently, it has shown that one kind of TEDs, dislocation arrays ͑DAs͒, can also be dissociated to form SFs, [12][13][14] although they have the lowest recombination activity. Thus, extensive studies are needed to clarify their dissociation behavior.…”
Section: Electron-beam-induced Current and Cathodoluminescence Study mentioning
confidence: 99%